The Effect of Peer Teaching Strategy and Simultaneous Round Table Strategy on Developing Speaking Skills in the Arabic Language among Seventh-Grade Students in Jordan - Odallah, Osama Omar Mahmoud; Al-Jarrah, Abdullah Azzam (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to reveal the effect of the strategies of peer teaching and the simultaneous round table in developing speaking skills in Arabic language among 7th grade students in Jordan. Methods: A quasi-experimental approach was used. The study sample consisted of 48 students from the 7th grade at The University School, which follows the Directorate of Private Education. The school was chosen purposively, and the study sample was divided into three groups: two experimental groups and a control group. The first experimental group was taught using the peer-teaching method, the second experimental group was taught using the simultaneous round table method, and the control group was taught using conventional methods. The speaking scale was used, and its validity and reliability were verified. Results: The study results showed statistically significant differences in the means of the three study groups on the speaking scale, indicating the effectiveness of the peer teaching strategy and the simultaneous round table strategy compared to conventional teaching. Conclusions: The study concludes that training courses should be conducted for Arabic language teachers in the upper basic stage to help them prepare and implement lessons using the peer teaching strategy and the simultaneous round table strategy.